Chirality Driven by Magnetic Dipole Response for Demultiplexing of Surface Waves. Issue 5 (12th September 2017) - Sinev, Ivan S.; Bogdanov, Andrey A.; Komissarenko, Filipp E.; Frizyuk, Kristina S.; Petrov, Mihail I.; Mukhin, Ivan S.; Makarov, Sergey V.; Samusev, Anton K.; Lavrinenko, Andrei V.; Iorsh, Ivan V.
Abstract : Spin angular momentum is an inherent feature of surface waves. Therefore, directional coupling of light to surface waves can be achieved with chiral nanoantennas. Leakage radiation microscopy measurements show that a simple dielectric nanoantenna provides chiral response with strong spectral dependence due to the interference of electric and magnetic dipole momenta when placed near a metal‐air interface. The proposed ultracompact device can be used for surface waves demultiplexing with high spectral resolution. Abstract: Surface electromagnetic waves are characterized by the intrinsic spin‐orbit interaction which results in the fascinating spin‐momentum locking. Therefore, directional coupling of light to surface waves can be achieved through chiral nanoantennas. Here, we show that dielectric nanoantenna provides chiral response with strong spectral dependence due to the interference of electric and magnetic dipole momenta when placed in the vicinity of the metal‐air interface. Remarkably, chiral behaviour in the proposed scheme does not require elliptical polarization of the pump beam or the geometric chirality of the nanoantenna. We show that the proposed ultracompact and simple dielectric nanoantenna allows for both directional launching of surface plasmon polaritons on a thin gold film and their demultiplexing with a high spectral resolution.